EARLY OUTCOME OF LICHTENSTEIN TECHNIQUE OF TENSION- FREE OPEN MESH REPAIR FOR INGUINAL HERNIA - Khan, Nadim; Naeem, Muhammad; Bangash, Adil; ullah, Asad; Sadiq, Muzaffaruddin; Hamid, Haris (Journal of Ayub Medical College Abbottabad, 2008)
Background: To evaluate the early outcome of Lichtenstein’s technique for repair of inguinal hernia using polypropylene mesh. Methods: This was a descriptive study conducted over a period of twelve months from 1st July 2007 to 30th June 2008 in Surgical ’˜B’ unit, Lady Reading Hospital, Peshawar. One hundred and twelve patients were received through the out patient department with diagnosis of inguinal hernia. Inclusion criteria was patients above the age of 18 years, reducible hernia, evidence of swelling in groin >2 months. Exclusion criteria was age less than 18 years, chronic constipation, chronic cough, symptoms of prostatism, irreducible hernia, obstructed hernia, strangulated hernia and patients with diabetes mellitus. All the patients were subjected to inguinal mesh repair using the Lichtenstein technique with polypropylene mesh. Results: Mean age of patients was 48.78±14.41 years. Sixty patients (53.6%) had right sided inguinal hernia while 46 patients (41.1%) had a left sided hernia and 6 patients (5.4%) had bilateral hernia. Sixty two patients (55.4%) had indirect hernia and 43 (38.4%) cases had direct hernia. Sixteen cases (14.3%) had previous history of surgery for hernia on the same side (recurrent hernia). Mild pain was observed in 53 cases (47.3%), moderate pain in 42 cases (37.5%), and severe pain in 17 cases (15.2%). Four patients (3.6%) in all developed a seroma Two patients (1.8%) developed a haematoma that required drainage. Three patients (2.7%) had a prolonged recovery and presented with abdominal distension. Five cases presented with infected wounds. Conclusion: Lichtenstein’s technique of inguinal mesh repair is a safe and effective procedure but emerging trends anticipates the implementation of day case surgery. Keywords: Inguinal hernia, Lichtenstein technique, open mesh repair, hernioplasty, Prosthesis.